A Flexible Terpyridine Derivative Interacts Specifically with G‐Quadruplexes. Issue 36 (28th July 2016) - De Rache, Aurore; Gueddouda, Nassima Meriem; Bourdoncle, Anne; Hommes, Paul; Reissig, Hans‐Ulrich; Mergny, Jean‐Louis
Abstract: G‐quadruplexes formed by nucleic acids are implicated in pathologies ranging from cancers to neurodegenerative diseases. We evaluated interactions of 29 bi‐ and terpyridine derivatives with G‐quadruplexes and duplexes. FRET‐melting, circular dichroism, and 1 H NMR spectroscopy showed that one terpyridine derivative interacted very selectively with G‐quadruplexes. This G‐quadruplex ligand inhibited helicase activity and should influence G‐quadruplex‐related biological processes. Abstract : The interaction of bi‐ and terpyridine derivatives with G‐quadruplexes is evaluated by FRET‐melting, circular dichroism, and 1 H NMR spectroscopy. One terpyridine derivative interacts very selectively with G‐quadruplexes and inhibits helicase activity.